Implementasi Sistem ERP Proses Sales Management Berbasis Odoo Dengan Metode Rapid Application Development Di UMKM Dapurbeta - Fajarrachman, Nandika; Budiyono, Avon (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Technological developments have a significant impact on Indonesian society, especially business actors. Digitalization of the sales process is important to improve performance and competitiveness, especially for MSMEs in the food and beverage industry. MSMEs can take advantage of digital technologies such as social media and Point of Sale systems to optimize marketing and sales. Dapurbeta, an MSME in the food and beverages sector, faces challenges in sales management which includes the sales process of catering, restaurants, TVS, and Motorist, which have not been integrated. Dapurbeta's marketing is still conventional, making it difficult to reach a wider market. To overcome this problem, Dapurbeta implemented an Odoo-based ERP system with rapid application development (RAD) research method. Odoo was chosen because of its ease of configuration according to Dapurbeta's needs. This research focused on fit and gap analysis and resulted in customized business processes, creating several modules, such as sales, point of sales, and social marketing. These modules are configured according to Dapurbeta's needs so that they are expected to increase sales and marketing.